Being a good neighbour: developing intercultural understanding through critical dialogue between an Australian and Finnish cross-case study. (1st November 2020) - Lobytsyna, Maria; Moate, Josephine; Moloney, Robyn
ABSTRACT: Language educators in Australia and Finland are expected to foster intercultural understanding within foreign language education. This paper presents findings from a qualitative case study focusing on theoretical and practical intercultural understanding in secondary school language education. The data for this study includes lesson observations as well as student and teachers interviews collected in two secondary schools in Australia and Finland. The findings demonstrate the complex resources teachers and students draw on to develop and share intercultural understanding. The discussion addresses the value of different perspectives and the need for a new metaphor to conceptualise intercultural understanding.